Research of Surface Reconstruction Method of Worm Gear Reverse Engineering based on Imageware and UG - Hongbin Yang; Guanyun Li; Ruiyi Li; Aijun Xu (Jixie chuandong)
The method of surface reconstruction is studied to realize the rapid reconstruction of the three-dimensional model of single-piece worm gear. Point cloud data is obtained by non-contact 3D scanner， and point cloud data is preprocessed and surface reconstructed by using reverse engineering software Imageware. The two methods of curve fitting surface and point cloud directly fitting the surface are mainly discussed， and the fitting precision and smoothness of the surface obtained by the two methods are compared， and the alignment of the reference coordinate system and subsequent solid modeling operations of the worm wheel three-dimensional model is completed in UG. The results show that the method of curve reconstruction surface can better meet the accuracy and smoothness requirements of the worm gear tooth surface. This method can quickly realize the accurate reconstruction of the three-dimensional model of the worm wheel， and a CAD model for the rapid remanufacturing of the worm wheel single piece and small batch is provided.